2013
DOI: 10.1016/j.cpcardiol.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Genotype- and Phenotype-Guided Management of Congenital Long QT Syndrome

Abstract: Congenital Long QT syndrome (LQTS) is a genetically heterogeneous collection of heritable disorders of myocardial repolarization linked by their shared clinical phenotype of QT prolongation on electrocardiogram and an increased risk of potentially life-threatening cardiac arrhythmias. At the molecular level, mutations in 15 distinct LQTS-susceptibility genes that encode ion channel pore-forming α-subunits and accessory/auxiliary subunits central to the electromechanical function of the heart have been implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
113
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 131 publications
0
113
0
3
Order By: Relevance
“…28 Although in our analysis the percentage of discordance was low, segregation analysis and/or functional studies are necessary to verify the pathogenicity or neutrality of these mutations. 28,37 Taking together, without validation, some of these mutations predicted as neutral or discordance will remain of uncertain significance, confounding genetic diagnosis.…”
Section: Pathogenicity Prediction With In Silico Toolsmentioning
confidence: 99%
“…28 Although in our analysis the percentage of discordance was low, segregation analysis and/or functional studies are necessary to verify the pathogenicity or neutrality of these mutations. 28,37 Taking together, without validation, some of these mutations predicted as neutral or discordance will remain of uncertain significance, confounding genetic diagnosis.…”
Section: Pathogenicity Prediction With In Silico Toolsmentioning
confidence: 99%
“…[23][24][25][26] Patients with a SCN5A mutation are well characterized, whereas those with mutations in CAV3, SCN4B, and SNTA1 less so, because they are very rare. 27 Because LQT3 is known for its high risk of fatal consequences caused by VF, confirmation of SCN5A mutation carriership is important for the prevention of future fatal arrhythmic events. Treatment with b-blockers is essential for patients with recurrent arrhythmic events, 28 although b-blockers are less effective than in LQT1 or LQT2.…”
Section: Long Qt Syndromementioning
confidence: 99%
“…According to a gene possessing mutations, LQTS has been classified into subtypes, of which LQT1, LQT2, and LQT3 are the most common. The first two types result from changes in the potassium channel genes KCNQ1 and KCNH2 (HERG), respectively, while LQT3 is caused by mutations in the gene SCN5A, encoding the sodium channel (Giudicessi & Ackerman, 2013b). The estimated prevalence of this disorder in Finland is 1:250 (Marjamaa et al, 2009), whereas in other populations it is reported to be 1:2000 (Schwartz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%